ANALISIS USAHATANI DAN NILAI TAMBAH TANAMAN PANGAN DI SUB DAS KEDUANG KABUPATEN WONOGIRI - , VERA IRIANA SIALLAGAN, Dr. Ir. Suhatmini Hardyastuti, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Decentralization policy through established regional autonomy requires each local government to be able to meet the needs of the region independently. The purpose of this study is (1) determine the feasibility of crop farming financially, (2) determine the feasibility of agro-food crops financially, and (3) identify value-added agro-products offood crops.The method used is descriptive analysis method. Population taken is farmers in Sub-watershed Keduang. Respondents interviewed farmers are 120 farmers selected simple random sampling. Respondent is a respondent agro commodities agro raw material rice, maize, cassava, and soybeans. The analytical method used was analysis of the feasibility and valueadded analysis. From the results of the study found that the farming rice, maize, and cassava is generally feasible to be developed, while soybean farming is not feasible. Seen from financial feasibility, general processing of food crops is also feasible to be developed because the result is higher than the standart of each feasibility criteria and provide added value too.